2020
DOI: 10.1186/s12913-020-05237-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding perceptions of involving community pharmacy within an integrated care model: a qualitative study

Abstract: Background: Over the past several years, there has been more emphasis on integration within health care. Community pharmacy is often under-represented within integrated care models. This study explored stakeholder perceptions and enablers of including community pharmacy within an integrated care model. Methods: A qualitative study was undertaken. Participants were recruited through professional networks and social media, as well as snowball recruitment from other participants. They included community pharmacis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This study offered similar results to ours regarding various discordant perceptions, concerns, and conflicts of interest. 29 However, we noted one formidable difference: nearly all developed countries have a perfect DS system in practice whereas, in Malaysia, this issue has emerged as a major barrier to collaboration. An important point to establish here is that the barriers to and facilitators of collaboration identified in this study are somehow similar to those enlisted in a recent systematic review that summarized factors affecting collaboration between CPs and GPs around the globe.…”
Section: Discussionmentioning
confidence: 90%
“…This study offered similar results to ours regarding various discordant perceptions, concerns, and conflicts of interest. 29 However, we noted one formidable difference: nearly all developed countries have a perfect DS system in practice whereas, in Malaysia, this issue has emerged as a major barrier to collaboration. An important point to establish here is that the barriers to and facilitators of collaboration identified in this study are somehow similar to those enlisted in a recent systematic review that summarized factors affecting collaboration between CPs and GPs around the globe.…”
Section: Discussionmentioning
confidence: 90%
“…This viewpoint is consistent with reports from other jurisdictions where pharmacists also perceived that their knowledge and skills are underutilized and unrecognized, and a sense that their professional identity was one of being ‘shopkeepers’. 20 , 44 With employers, a lack of acknowledgement of their professional expertise together with the deficits in support, augmented the perception of being undervalued. Aspden et al (2021) reported similar viewpoints from New Zealand pharmacists who reported a lack of recognition of pharmacy from the public and other healthcare professionals in addition to lack of support from management within the profession itself.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing recognition that integrating care can improve patients’ outcomes, especially among those with complex health and social needs [ 25 ]. By ensuring communication and collaboration between professionals of various organisations, and the participation of every stakeholder, case managers are “searching for connections between the healthcare system and other human service systems to improve outcomes”, which correspond precisely to the definition of integrated care as stated by Leutz [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacies are private organisations committed to maintaining the overall health of their patients through a variety of interventions: medical information review and treatment follow-up, preparation of medication, adjustment and initiation of treatment, and daily consultations with people who have questions [ 23 ]. Community pharmacists are indispensable partners for patients with polypharmacy [ 24 , 25 ]. They educate and advise people on the use of over-the-counter or prescribed medication and natural health products; support people seeking solutions to minor health problems; contribute to patients’ education regarding healthy lifestyles; and if necessary, refer patients to other health and social services [ 23 ].…”
Section: Introductionmentioning
confidence: 99%